Analisis Efektivitas Biaya Pengobatan DM Nefropati di RSUD Panembahan Senopati Bantul - Sumiyati, Putri; Nurinda, Eva; Indrayana, Sofyan; Dwinta, Eliza (Indonesian Journal of Hospital Administration, 2025)
Diabetes mellitus is a group of metabolic diseases characterized by increased blood glucose. Diabetes mellitus can cause various chronic complications, one of which is diabetic nephropathy. The number of uses of treatment will cause differences in the effectiveness and cost of therapy.This study determined the cost effectiveness of nephropathy DM treatment in the Inpatient Ward of Panembahan Senopati Hospital, Bantul. This study was an analytic observational study with retrospective. Data collectional by looking at medical record and administrative data. As many as 63 respondent were inclusion criteria. The data obtained were analyzed using Microsoft Excel. Treatment effectiveness was measured based on patients who achieved ≤200 mg/dL Current Blood Sugar (GDS), while cost effectiveness was measured based on ACER and ICER values. The results showed that the effectiveness of drug B (non-insulin) was 88%, while drug A (insulin) was 85%. The average total cost of anti-diabetic drug B (non- insulin) is Rp. 839,563, and drug A (insulin) Rp. 1,163,473. drug group B (non- insulin) is more cost effective with an ACER value of Rp. 954,048, compared to drug A (insulin) of 1,368,791, in nephropathy DM patients at Panembahan Senopati Hospital, Bantul. The conclusion of this study shows that drug therapy group B (non- insulin) can be used as a cheaper and more effective treatment option for nephropathy DM patients